Analysis of Service Time Waste Using Lean Healthcare Method in the Neurology Outpatient Clinic : Analisis Pemborosan Waktu Pelayanan dengan Metode Lean Healthcare di Poli Syaraf - Fauzia, Lavina Felda; Aryanny, Enny (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Healthcare organizations must reduce non–value-added (NVA) activities to improve patient experience and resource efficiency; Specific Background: the neurology outpatient clinic of Hospital XYZ experiences prolonged service cycles; Knowledge Gap: evidence is limited on combining end-to-end process mapping with structured risk prioritization to target time waste in outpatient pathways; Aims: this study identified dominant wastes and designed improvements using Lean Healthcare tools (Big Picture Mapping) and FMEA; Results: the baseline total service time was 9,158 s (2.54 h) with value-added time 837 s (9.14%) and NVA 89.99%, while the proposed future state reduced NVA time to 5,038 s (1.40 h) and increased value-added time to 16.61%; Novelty: the work integrates BPM-derived waste quantification with FMEA-based prioritization to translate waste diagnosis into actionable redesign; Implications: implementing streamlined registration (including online access), standard work, and routine facility maintenance can shorten outpatient lead time and support continuous quality improvement. Highlights: Baseline pathway shows very high NVA time (89.99%) versus value-added time (9.14%). Proposed future state cuts NVA time to 5,038 s (1.40 h) and raises value-added time to 16.61%. BPM + FMEA provides a practical workflow to quantify waste and prioritize fixes. Keywords: Lean Healthcare, Big Picture Mapping, FMEA, Outpatient Clinic, Service Time Waste